(untitled) (Academia Science Repository, 2023)
During the process of teaching, a lot of different and useful methods are applied. Teachers employ several learning techniques as the means through which they acquire information and knowledge. These insights come to them through their surroundings and other individuals. It is required from teachers to be qualified and should also have teaching methodology structured in such a way that is new and brings good results in order to teach and educated and experienced students and should also be structured in such a way that the teaching methodology is advanced as well as bringing good results. Thus, teaching method plays a much larger and more significant role in the educational process. In this article, issues such as a new and integrated teaching system, working with it in which strategy, approaching students in a latest approach are discussed. Since the integrative style is considered to be a new mechanism, in the process of writing this report, a huge and new database was found, since the Integrative style was considered a new style.